Pengembangan Motivasi Kinerja Guru Dalam Implementasi Kurikulum Merdeka Di SMP PAX ECCLESIA Bekasi - Julinda Siregar; Soeparlan Kasyadi; Chandra Sagul Haratua; Labora Marbun (AMMA : Jurnal Pengabdian Masyarakat, 2024)
The purpose of this activity is to help PAX Ecclesia Middle School teachers to develop performance motivation in implementing the independent curriculum and to accept every change with the aim of improving the quality of education. After the teachers participated in the in-house training on developing teacher performance motivation in implementing the curriculum, the PkM team conducted an interview with the Principal to find out the changes seen in teacher behavior, especially in work enthusiasm. The In-House Training event went smoothly and the teachers were very happy and enthusiastic to listen to the presentation of material from the speakers. The Principal also explained that the teachers were happy with the PkM activities carried out by the Unindra Postgraduate Lecturer. The resource person explained that the independent curriculum is a curriculum that has been presented flexibly, and implemented with a fun, enjoyable and enjoyable teaching model. Furthermore, the speakers also said that in order to be able to innovate, teachers must continue to develop themselves through training, seminars, workshops and also further studies.